Tinjauan Perspektif Behaviorisme terhadap Kegiatan Ekstrakurikuler Kepramukaan di SD Negeri 1 Simo Boyolali - Harindra Dina Natamia; Fitria Unzurna; Endang Fauziati (LPPM Universitas Negeri Yogyakarta, 2022)
This study aims to describe the perspective view of Albert Bandura's behaviorism on scouting extracurricular activities at SD Negeri 1 Simo Boyolali. This study used descriptive qualitative method. Data collection techniques using observation, interviews, and documentation. This study uses an interactive model of data analysis techniques. The results showed that the implementation of Albert Bandura's theory of the process of observing and imitating can influence a person's behavior. Changes in the behavior of students who initially acted less disciplined, became more disciplined. Students can build their knowledge based on their experiences which can be seen in their characteristic behavior. In an effort to build character, students can take part in scout extracurricular activities at school. Scout extracurricular activities in Indonesia are mandatory extracurricular activities in the 2013 curriculum (K13). The implementation of scout extracurricular activities is guided and coached by scout coaches, teachers, and also the principal as a cameraman who is responsible for all activities in the school including scout extracurricular activities. Scout extracurricular activities are interesting, challenging, and fun. These activities are a form of character representation that will be formed by scout extracurricular activities. So that it can construct student characters that have an impact on students' daily lives.